MINAT BERINVESTASI MAHASISWA DAN KUALITAS PELAYANAN GERAI BURSA EFEK INDONESIA STIE KESATUAN BOGOR - Heri Sastra (Forum Dosen Indonesia, 2018)
Service Quality has effect on investing intention. Student motivation in investing will be awakened by the service quality. The Purpose of this study was to determine the factors that influence the students’ intention in investing. This study was conducted in BEI Investment Gallery of STIE Kesatuan with 260 students as respondents. Data were analyzed using General Liniear Model. The results showed that the program, classes, Employment Status, Gender, Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy simultaneously affect the interest Invest Students. Keywords: Investing Intention, Student, Galeri Investasi BEI, Service Quality.